DESIGN OF BASES AND FOUNDATIONS ON SALINY SOILS - Maxsimov Kasimkhan Ibaevich (Journals Park Publishing, 2023)
The influence of aggressiveness and variability of the properties of saline soil on the performance of bases and foundations was studied. Materials with non-corrosive properties are given. Electrokinetic stabilization reduces the salt content in soils and increases its bearing capacity.
Keywords: saline soils, suffusion, concrete corrosion, fiber polymers, electrokinetic stabilization, green infrastructure, protective coatings.